GENETIC DISSIMILARITY OF SOYBEAN CULTIVARS AND ITS INTERRELATIONS WITH AGRONOMIC ATTRIBUTES - Scarton, Victor Delino Barasuol; Ivan Ricardo; Roza, João Pedro Dalla; Bruinsma, Gabriel Mathias Weimer; Bandeira, Willyan Junior Adorian; Pradebon, Leonardo Cesar; Loro, Murilo Vieira; Colet, Christiane de Fatima; Sangiovo, Jaqueline Piesanti; Silva, José Antonio Gonzalez da (REVISTA DE AGRICULTURA, 2025)
The objective of this study was to reveal the genetic dissimilarities between cultivars and their interrelationships with agronomic attributes in the northwest region of the state of Rio Grande do Sul. The study was developed in 2023/2024, at the Escola Fazenda da Universidade Regional do Noroeste do Estado do Rio Grande do Sul, located in Augusto Pestana, in the state of Rio Grande do Sul, Brazil. The experimental design used was a randomized complete block design, with 43 soybean cultivars arranged in five replicates per cultivar, totaling 215 experimental units. The experimental units consisted of seven sowing lines, with spacing of 0.5 meters and 15 meters in length, totaling 52.5 m2. Sowing was carried out in the first half of November 2023 with a sowing density of 16 seeds m-1 and base fertilization with 250 kg ha-1 in the formulation 05-20-10. Phytosanitary management was carried out in order to minimize the biotic effects on the results of the experiment. Abiotic factors such as air temperature and precipitation were not limiting for the development of the cultivars, with no effects on grain yield, number of pods on the main stem, number of total pods and seed mass per plant. The cultivars are dissimilar regarding cotyledon retention, root system depth, cotyledon damage, seed mass per plant and grain yield. The cultivars BRASMAX 66 E and FTR 1554 IPRO are the most productive and dissimilar to the other cultivars for the Northwest Region of Rio Grande do Sul.